TINGKAT KEAMANAN CEREBRAL DIGITAL SUBSTRACTION ANGIOGRAPHY PADA ANAK DI BEBERAPA RUMAH SAKIT DI INDONESIA - Fritz Sumantri Usman, Achmad Firdaus Sani, Yuwono, Ashari Bahar, Tommy Rachmat Setyawan, Iskandar Na (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTIONTHE PREVALENCE OF STROKE IN CHILDREN BETWEEN 611 PER 100000 CHILDREN CEREBRAL DIGITAL SUBSTRACTION ANGIOGRAPHY CEREBRAL DSA IS THE GOLD STANDARD PROCEDURE FOR ASSESSING VASCULAR ABNORMALITIES OF THE BRAIN HOWEVER IT IS AN INVASIVE PROCEDURE AND IS RELATIVELY EXPENSIVE UNTIL NOW THERE HAVE BEEN NO REPORTS OF COMPLICATIONS OF CEREBRAL DSA IN CHILDREN